PEMIKIRAN MODERNISASI KH MASRUR MUSIR DI SUNGAI LILIN MUSI BANYUASIN - Catur Catur (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 2022)
This thesis examines the Modernization Thought of KH Masrur Musir Sungai wax Musi Banyuasin. Problems The writing of this thesis was prepared using a qualitative method. The approach used is a historical approach, researchers use the theory of continuity. The theory explains the problem of sustainability in the midst of renewal. Renewal occurs when new traditions emerge that are stronger than before. Although, the renewal that occurs will not be interrupted instantly, there is still a continuation of the old tradition despite the existence of new ideas. From the results of the study it can be concluded that: KH. Masrur Musir had a very important role for the Sungai candle community at that time establishing the Assalam madrasa which was the first Islamic boarding school in Sungai wax. 1). KH. Masrur Musir is a pioneering scholar of Islamic education, an intelligent educator, has advanced thinking in reading the conditions in subsequent developments, especially in Islamic education. He was determined to make reforms even though many were opposed by the community and teachers at that time. 2). KH. Masrur Musir carried out modernization because he assessed and observed the phenomenon of Islamic society. namely not being able to realize between Islamic religious education and general education, because at that time all Islamic educational institutions did not yet exist to protect general subjects. He has the thought that if the world of education, especially Islamic education continues to be left without any renewal and improvement of the education system, the world of Islamic education will one day experience a gloomy period, especially in the Sungai wax area. 3). KH. Masrur Musir gave many new understandings of Islam to the Sungai candle community including, he introduced general lessons at the Assalam madrasa. At that time the madrasas did not have a general lesson. Because the ulema want to focus the students so that they really understand the teachings of Islam. However, KH. Masrur Musir was present and had forward thinking at the time that if the world of education, especially Islamic education, continued to be left without any renewal and improvement of the education system, the world of Islamic education would one day experience a bleak period. In fact, it is proven that at this time many madrasas are no longer functioning.